If the length is taken as l , height is taken as h and breadth is taken as b . then
Area of the rectangular prism= 2( (l*b) + (b*h) + (h*l) )
hope that helps
M = (y2-y1)/(x2 -x1)
m = (7 -2)/(5 - 1)
m = 5/4
answer: slope m = 5/4
Answer:
59
Step-by-step explanation:
Simplify the following:
5 + 9 (2 + 4)
2 + 4 = 6:
5 + 9×6
9×6 = 54:
5 + 54
5 + 54 = 59:
Answer: 59
Answer:
81
Step-by-step explanation:
u multiply 9 x 9 not 9x2
Answer:
A. It Increases
Step-by-step explanation:
Given the expression:
1+3f
When f=1, 1+3f=1+3(1)=1+3=4
When f=2, 1+3f=1+3(2)=1+6=7
When f=3, 1+3f=1+3(3)=1+9=10
We can see that the value of the given expression for each successive term increases and in fact form the sequence
4,7,10,...
Therefore, when f increases, 1+3f increases.